I am the shark - Holub, Joan; Keller, Laurie (Crown Books for Young Readers, 2021)
"Humorously illustrated sharks introduce themselves and the characteristics that make them special, in a child-friendly, fish-out-of-water tale that includes profiles of species ranging from the Great White and Greenland to the Mako and Hammerhead"--
Keywords: Sharks -- Juvenile literature; Ocean -- Juvenile literature; Marine animals -- Juvenile literature; Sharks; Ocean; Marine animals; Picture books; Picture books